STABILITY-INDICATING REVERSED-PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE SIMULTANEOUS ESTIMATION OF DARUNAVIR AND RITONAVIR - D, Sindu Priya; Sankar D, Gowri; Sk, Masthanamma (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective of the proposed study was to develop and validate a new stability indicating reverse phase high performance liquid chromatography method for the simultaneous estimation of darunavir (DRV) and ritonavir (RTV). Methods: The method was optimized using Atlantis C18 column (50 mm×4.6 mm, 5 µm, Waters Corporation, Milford, USA). Acetonitrile and water were used as mobile phase in the proportion of 60:40. The flow rate was 0.8 ml/minutes and the effluent was monitored at 230 nm. Results: The retention time of DRV and RTV was 3.15 minutes and 4.59 minutes, respectively. The method was precise as it showed a % relative standard deviation of <2%. The percentage recoveries of both the drugs DRV and RTV were 99.8-100.01% and 99.5-99.97%, respectively. The linearity of DRV and RTV was in the range of 40-120 and 4-20 µg/ml, respectively. Calibration curve showed good linearity and range. The correlation coefficient of DRV and RTV was 0.999 each. Moreover, the results obtained for limit of quantification, limit of detection, robustness, and ruggedness were well within the acceptance criteria. Conclusion: The proposed method was found to be simple, rapid, accurate, precise, and stability indicating. It was found to be economical and suitable for simultaneous determination of DRV and RTV which is can also be applied for pharmaceutical dosage form. Keywords: Darunavir, Ritonavir, Reversed-phase-high performance liquid chromatography, Simultaneous estimation, Forced degradation.